Consumo de levonorgestrel expendido en el establecimiento farmacéutico de la cadena de boticas Mifarma del Porvenir, enero 2015 – diciembre 2015 - Meregildo Baca, Rossy Ivón (2016)
In the present work Mifarma of the District carried out a study of the consumption of levonorgestrel as oral contraceptive of emergency expended in the pharmaceutical establishment of the Chain of Medicines. The Future during the period in January to December 2015, According to trade name (NOGESTROL 1.5 mg; LINDIOL 1.5mg, 1.5mg POSTINOR; AUXXIL 0.75 mg, 0.75 mg POSTINOR) régimen of dosing (one dose of 1.5 mg or two doses of 0.75 mg c / 12h) and cost. The information obtained of the Computerized registration system Boticas pharmaceutical establishment Mifarma study found that in the months from January to May was the best-selling brand AUXXIL 0.75 mg with a total of 59 boxes at a price of S /. 22.50 reporting consumption S /. 1327.50; and between the months of June to December was the best-selling brand NOGESTROL 1.5 mg with a total of 211 boxes at a price of S /. 15.40 reporting consumption S / .3249.40. The trademark most sold throughout the year was 1.5 mg NOGESTROL reporting the highest annual consumption